Space Needle (Ellis Post Card Co.)
Seattle's $4,000,000.00 Space Needle. This close up view shows the top of the Needle which has two decks. The upper, or observation deck, is stationary, while the one below, on which is located a modern restaurant, rotates once every hour, affording an ever changing view of Mountains, Lakes, City and Harbor. Lake Union may be seen in the immediate background, while in the distance is the Seattle-Everett Freeway under construction. One of the three elevators may be seen approaching the top landing.